Analysis of The Cash Flow Statement in Assessing The Financial Performance of The Khazanah Insan Mulia Sharia Cooperative - Maysharah Maysharah; Laylan Syafina; Kamilah Kamilah (Cakrawala Repositori IMWI)
This research aimed to analyze the cash flow statement as a tool for assessing the financial performance of the Khazanah Insan Mulia Sharia Cooperative. The analysis focused on four cash flow ratios, namely the Operating Cash Flow Ratio (OCF), Cash to Total Debt Ratio (CTD), Capital Expenditure Ratio (CER), and Cash Flow Coverage Ratio (CFCR), during the 2023–2025 period. The study employed a descriptive quantitative approach using cooperative financial statement data, including contribution receipts, principal deposits, loan activities, and operational expenditures. The results indicated that the cooperative’s financial performance was in a healthy condition, demonstrating an improving trend over the observation period. The cash flow statement provided a clearer overview of the cooperative’s liquidity, solvency, and financial management efficiency. Based on these findings, it can be concluded that the Khazanah Insan Mulia Sharia Cooperative demonstrated healthy financial performance with a continuous improvement trend from 2023 to 2025. In 2023, the cooperative was able to fulfill its short-term obligations effectively; in 2024, it experienced significant improvement through stronger operating cash flow performance; and in 2025, its financial condition became more stable, with no outstanding obligations, debt, or significant financial burdens, resulting in a strong cash position and a highly favorable liquidity condition. These findings highlight the importance of cash flow statement analysis as a basis for strategic decision-making to improve cooperative performance and long-term sustainability.